Дизайн В. Г. Кричевського: ретроспектива та сучасна трансформація - Радомська, В. Р.; Гаврисьо, С. Р.; Radomska, V.; Havryso, S. (Видавництво Львівської політехніки, 2017)
У статті розглянуто ретроспективу дизайну В. Г. Кричевського періоду 1891–1943 рр. та запропоновані шляхи трансформації, інтерпретації доробку митця в сучасний урбаністичний дизайн. Проектні пропозиції сформовані для покращення та зміни естетичної складової навчальних корпусів та ландшафтного простору Національного університету “Львівська політехніка”.

For the formulation task of design updating and modernization of aesthetically old buildings of academic buildings, library of Lviv Polytechnic National University (70–80's. XX century.), was elected transformation method and interpretation of iconic developments Ukrainian artists – designers. For this purpose, selected art of V. G. Krychevsky (1872–1952). Original author aesthetics and stylization of ethnic motif in the context of Art Nouveau style, whose representatives were a large galaxyof artists in Ukraine in late XIX – the first quarter of the twentieth century, most naturally suited to this task. For integrate motives of Krichevsky in urban environment were used objects: residential architecture on the Hlyboka street , with a proposal mosaic on the side of the wall; Lviv Polytechnic University Library on the Square of St. George, with a proposal murals; academic buildings №1 and №5 of Lviv Polytechnic with proposals murals in the exterior and interior; decorative forged railing for decoration of the bench near academic building № 2 of Lviv Polytechnic in the recreational landscape zone. Developments of Krichevsky – is the actual material of analogs, which in the hands of a skilled designer relayed in modern design in a new perspective. The unique of ornamental schemes by V. Krychevsky is represented – transforming small size circuits and samples of printed products to increased tenfold, scale of decorative – monumental compositions (mural, sgraffito, graffiti, mosaics, decorative printing banners, etc.), the structure and aesthetic component of the original not violated. Generally, the transformation of achievements known artists, designers and architects previous eras have of great methodological significance for the development of a young designer and form his identity in the future. For the development and identification of cities in Ukraine this experience has a double benefit: functional, figurative and stylistic and because it allows you to promote and integrate the achievements of Ukrainian genial creators in the modern environment. Trying to inspire graphic design of V. Krychevsky a modern urban environment will contribute to the aesthetics and identification of selected objects and landscape space.
Design of V. G. Krychevsky: retrospective and modern transformation
Keywords: В. Г. Кричевський; дизайн; мистецтво; композиція; інтер’єр; стінописи; предметне середовище; Національний університет “Львівська політехніка”; V. G. Krychevsky; design; art; composition; interior; murals; presentive environment; Lviv Polytechnic National University; 004.9